Resilience and stress as predictors of work engagement: the mediating role of self-efficacy in nurses - Cabrera-Aguilar, Elard; Zevallos-Francia, Margarita; Morales-García, Mardel; Ramírez-Coronel, Andrés Alexis; Morales-García, Sandra B.; Sairitupa-Sanchez, Liset Z.; Morales-García, Wilter C. (Frontiers in Psychiatry, 2023)
Background: Nurses face high levels of stress and work demands, which can affect their work engagement and psychological well-being. Resilience and self-efficacy have been identified as important resources to improve nurses' adaptation and work engagement. Objective: This study aimed to evaluate the mediating role of self-efficacy in the relationship between resilience and stress on work engagement in Peruvian nurses. Methods: A cross-sectional design was used, and data were collected from a sample of 459 nurses. Self-report questionnaires were administered to measure selfefficacy, resilience, stress, and work engagement. SEM analyses were performed to examine the relationship between these variables, and a mediation analysis was conducted to evaluate the role of self-efficacy as a mediator in the relationship between resilience, stress, and work engagement. Results: The results indicated a positive relationship between resilience, self-efficacy, and work 2 This is a provisional file, not the final typeset article engagement, as well as a negative relationship between stress and work engagement. Additionally, self-efficacy mediated the relationship between resilience and work engagement, as well as the relationship between stress and work engagement in nurses. Conclusions: Personal resources such as self-efficacy are a key factor in the relationship between resilience (work resources), stress (work demands), and work engagement of Peruvian nurses. Strengthening self-efficacy and resilience can improve work engagement and personal satisfaction of nurses. Hospital administrators and nursing managers should consider the importance of resilience, stress, work engagement, and self-efficacy in registered nurses and develop effective strategies to improve them. This can have a positive impact on the quality of care provided to patients and on the job satisfaction of nurses.